Mexikid : A Graphic Memoir - Martin, Pedro, 1967- (New York : Dial Books for Young Readers, 2023)
"Pedro Martin's grown up in the U.S. hearing stories about his legendary abuelito, but during a family road trip to Mexico, he connects with his grandfather and learns more about his own Mexican identity in this ... graphic memoir"--
Keywords: Martin, Pedro, -- 1967- -- Comic books, strips, etc; Martin, Pedro, -- 1967- -- Cartoons and comics; Mexican Americans -- Biography; Identity (Psychology) -- Comic books, strips, etc; Mexican Americans -- Biography; Identity -- Cartoons and comics; Cartoons and comics; Autobiographical comics; Graphic novels